Struktur Naratif Cerita Rakyat Tapah Malenggang Kabupaten Batanghari, Provinsi Jambi - Irma Suryani; Dwi Rahariyoso; Nurfitri Susanti (Universitas Batanghari Jambi, 2021)
This research describes the narrative structure of Tapah Malenggang folklore based on the transcription conducted by Datuk Rasyid from the utterances of Datuk Zainul and Datuk Saharman. The folklore of Tapah Malenggang, as part of the oral literature of the Batanghari people, is gradually shrinking, and it can even be said to be on the verge of extinction. Through this research, it is hoped that the form and structure of the Tapah Malenggang folklore can be known. The method used is descriptive analysis. The results showed that the Tapah Malenggang story was in the form of myths and its narrative structure, namely the characters and settings functioned structurally to formulate the folklore as myth.